Synthesis, characterisation and evaluation on the performance of ferrofluid for microplastic removal from synthetic and actual wastewater - Hamzah, Sofiah; Lau, Yuke Ying; Abd. Rahman Azmi, Alyza Azzura; Razali, Nurul Ashraf; Hairom, Nur Hanis Hayati; Mohamad, Nurul Aqilah; Che Harun, Mohammad Hakim (Elsevier, 2021)
Synthesis of ferrofluid without the addition of stabilizing agents or surfactants is an innovation of new method for microplastic removal. This study focuses on the ability of several types of oils as carriers and how they may improve the removal efficiency of the microplastic. The method is relatively low cost, simple and sustainable. The formation of ferrofluid involved the mixing of oil and iron oxide powder. The experimental work was commenced by adding 2 mm polyethylene terephthalate (PET) microplastics into synthetic ferrofluid. Then, the removal efficiency of microplastics was examined by varying the elements of ferrofluid based on three specific parameters, namely type of oil, volume of oil and dosage of iron oxide to obtain a standard formulation of the optimum results. Overall findings of the study indicated that the optimum formulation for ferrofluid preparation was at a ratio of 1:2.5 (volume of oil: dosage of magnetite) using lubricating oil which has successfully removed 99% of microplastic from water media. Subsequently, the physical and chemical properties of the prepared ferrofluid were also analysed using scanning electron microscope (SEM) and Fourier transform infrared (FTIR) spectroscopy. Performance evaluation of the prepared ferrofluid on actual wastewater (laundry wastewater) revealed that 64% of microplastics were removed after treatment.